Light control of orbital domains: case of the prototypical manganite La0.5Sr1.5MnO4. (14th November 2016) - Miller, Timothy; Gensch, Michael; Wall, Simon
Abstract: Control of electronic and structural ordering in correlated materials on the ultrafast timescale with light is a new and emerging approach to disentangle the complex interplay of the charge, spin, orbital and structural degree of freedom. In this paper we present an overview of how orbital order and orbital domains can be controlled by near IR and THz radiation in the layered manganite La0.5 Sr1.5 MnO4 . We show how near-IR pumping can efficiently and rapidly melt orbital ordering. However, the nanoscale domain structure recovers unchanged demonstrating the importance of structural defects for the orbital domain formation. On the contrary, we show that pulsed THz fields can be used to effectively orientate the domains. In this case the alignment depends on the in-plane electric field polarisation and is induced by an energy penalty that arises from THz field induced hopping of the localised charges.